Integrated indicators for assessment of best management practices in tilapia cage farming - Portinho, Jorge Laço [UNESP]; Silva, Mariana S.G.M.; Queiroz, Julio Ferraz; de Barros, Inácio; Campos Gomes, Ana C.; Losekann, Marcos Eliseu; Koga-Vicente, Andrea; Spinelli-Araujo, Luciana; Vicente, Luiz Eduardo; Rodrigues, Geraldo Stachetti (Elsevier, 2021)
The aim of this study is to present APOIA-Aquaculture, an indicator system for assessing Best Management Practices (BMPs) in tilapia cage farming. Two specific objectives were set: (1) to detail the construction and operation of APOIA-Aquaculture; and (2) to attest to its analytical feasibility for BMP assessment in six fish farms selected as contrasting ventures at the Furnas and the Ilha Solteira reservoirs, important production sites in Southeastern Brazil. The proposed APOIA-Aquaculture comprises 68 integrated indicators, grouped into a set of four managerial dimensions: Spatial Organization (22 indicators), Management and Nutrition (23), Water Quality (14), and Quality of Sediment (9). The indicators were devised as to express fish farm compliance to predefined environmental standards, selected legislation requirements, and BMP effectiveness. Results of farm assessments indicate common deficiencies in the indicators of the Spatial Organization dimension, such as those related to the lack of equipment for water quality monitoring, fish cage positioning, improper storage of feed and supplements, inadequate control of fish disease symptoms, lack of appropriate records of the use of therapeutic and prophylactic products, and conflicts related to multiple water uses. In the Management and Nutrition dimension, indicators stressed the absence of biometric checks, inadequate procedures for residue disposal, and deficient control and records of fish losses (escapes). Overall, interactions were observed among indicators of the Management and Nutrition dimension and signs of deterioration in Water and Sediment Quality, as a consequence of inadequate feeding practices. Based on our results, we demonstrate the efficacy of APOIA-Aquaculture as an analytical tool for assessment of BMPs in tilapia cage farming. Aggregate information from indicators facilitates the adoption of measures to promote specific local infrastructure and monitoring needs according to proposed BMPs, towards improving the sustainability of the fish farms.
Keywords: Aquaculture; BMPs; Impact assessment; Tropical reservoir; Water quality